Siloxane composition, electrophotographic member, method for manufacturing electrophotographic member, process cartridge and electrophotographic image forming apparatus
A siloxane composition with specific organopolysiloxanes and carbon blacks addresses C-set issues in electrophotographic developing rollers, ensuring stable and high-quality image formation by enhancing carbon black affinity and reducing plastic deformation.
Patent Information
- Application Number
- JP2021090060
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-05-28
- Publication Date
- 2024-12-23
- Estimated Expiration
- 2041-05-28
AI Technical Summary
The existing electrophotographic developing rollers made of silicone rubber experience plastic deformation (C-set) in high temperature and high humidity environments, leading to uneven toner transport performance and density issues in electrophotographic images.
A siloxane composition comprising specific organopolysiloxanes, carbon blacks with varying surface areas, and an organohydrogenpolysiloxane, which when cured, forms a conductive elastic layer with enhanced affinity to carbon black, reducing gaps and plastic deformation.
The solution provides a conductive elastic layer that minimizes C-set, ensuring stable and high-quality electrophotographic image formation by maintaining consistent toner transport performance.
Smart Images

Figure 0007604324000025 
Figure 0007604324000026 
Figure 0007604324000027
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a siloxane composition, an electrophotographic member, a method for producing an electrophotographic member, a process cartridge, and an electrophotographic image forming apparatus. [Background technology]
[0002] Silicone rubber has stable rubber elasticity over a wide temperature range compared to natural rubber and other synthetic rubbers, and changes in physical properties due to temperature are small. Silicone rubber is also excellent in heat resistance, cold resistance, weather resistance, and ultraviolet resistance, and is therefore widely used in the fields of electrical and electronic industries, construction and civil engineering, automobiles, general household products, and the like. In particular, addition-curing liquid silicone rubber, which is cured by hydrosilylation, can be cured in a short time and has small curing shrinkage, so it is used in various members in the electrophotographic field, which requires high dimensional accuracy. For this reason, electrophotographic members having an elastic layer using silicone rubber and a highly wear-resistant surface layer around the periphery of the elastic layer to impart durability are preferably used.
[0003] When electrophotographic members require electrical conductivity, the silicone rubber elastic layer may be formed of conductive silicone rubber with an added conductive agent. As an electrophotographic member having such a configuration, Patent Document 1 discloses a developing roller having a silicone rubber elastic layer containing two types of carbon black with different DBP absorption amounts. In addition, it is disclosed that in such a developing roller, carbon black with a low specific surface area is distributed near the surface of the elastic layer to provide a conductive path on the surface of the elastic layer, and carbon black with a high specific surface area contributes to the formation of a conductive path from the surface of the elastic layer to the conductive mandrel, and as a result, the charge-up of the developing roller can be suppressed. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-45012 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, when a contact member such as a toner regulating blade is brought into contact with a specific position on the surface of the developing roller in the developing roller of Patent Document 1 for a long period of time under a high-temperature and high-humidity environment such as a temperature of 40° C. and a relative humidity of 95%, plastic deformation (hereinafter also referred to as "C set") that is not easily restored may occur in the contact portion. The portion where the C set occurs has different toner transport properties from other portions. Therefore, when an electrophotographic image is formed using such a developing roller, density unevenness due to the C set may occur in the electrophotographic image.
[0006] One aspect of the present disclosure is directed to providing a siloxane composition that provides a conductive elastic layer that is unlikely to cause C-set even when in contact for a long period of time. Another aspect of the present disclosure is directed to providing an electrophotographic member having a conductive elastic layer that is unlikely to cause C-set even when in contact for a long period of time. Still another aspect of the present disclosure is directed to providing a process cartridge that contributes to the stable formation of high-quality electrophotographic images. Yet another aspect of the present disclosure is directed to providing an electrophotographic image forming apparatus that can stably form high-quality electrophotographic images. [Means for solving the problem]
[0007] According to one embodiment of the present disclosure, there is provided a siloxane composition comprising the following components (A) to (D): (A) an organopolysiloxane consisting of the following components (A-1) and (A-2): (A-1) Organopolysiloxane represented by the following average composition formula (1):
[0008] [ka]
[0009] (In the average composition formula (1), R1 each independently represents an alkyl group having 1 to 10 carbon atoms, R2 each independently represents an alkenyl group having 2 to 8 carbon atoms, and m is a number of 1,000 or more and 2,000 or less.)
[0010] (A-2) Organopolysiloxane represented by the following average composition formula (2):
[0011] [ka]
[0012] (In the average composition formula (2), R3's each independently represent an alkyl group having 1 to 10 carbon atoms, R4's each independently represent an alkenyl group having 2 to 8 carbon atoms for each repeating unit, о is a number from 10 to 45, and n+о is a number from 300 to 500.) (B) Specific surface area is 60m 2 / g or more 100m 2 A first carbon black having a molecular weight of 1 / g or less; (C) Specific surface area is 12 m 2 / g or more 30m 2 / g or less of a second carbon black; (D) Organohydrogenpolysiloxane represented by the following average composition formula (3):
[0013] [ka]
[0014] (In the average composition formula (3), R5 each independently represents an alkyl group having 1 to 10 carbon atoms, p is a number of 3 or more and 20 or less, and q is a number of 4 or more and 20 or less.) The ratio of the component (A-2) in the component (A) is from 0.1% by mass to 5.0% by mass, the ratio (C2 / C1) of the content C2 of the second carbon black to the content C1 of the first carbon black is from 2.0 to 25.0, and the total amount of the first carbon black and the second carbon black relative to the siloxane composition is from 10% by mass to 30% by mass.
[0015] According to another aspect of the present disclosure, there is provided an electrophotographic member having a substrate and an elastic layer on the substrate, the elastic layer being a cured product of the above-mentioned siloxane composition. According to another aspect of the present disclosure, there is provided a method for producing an electrophotographic member having a substrate and an elastic layer on the substrate, the method comprising the step of curing a layer of the above-described siloxane composition to form the elastic layer.
[0016] According to another aspect of the present disclosure, there is provided a process cartridge including the electrophotographic member described above and configured to be detachably mountable to a main body of an electrophotographic image forming apparatus. According to yet another aspect of the present disclosure, there is provided an electrophotographic image forming apparatus having an image carrier for carrying an electrostatic latent image, a charging device for primarily charging the image carrier, an exposure device for forming an electrostatic latent image on the primarily charged image carrier, a developing device for developing the electrostatic latent image with toner to form a toner image, and a transfer device for transferring the toner image to a transfer material, wherein the developing device has the above-mentioned electrophotographic member. Effect of the Invention
[0017] According to one aspect of the present disclosure, a siloxane composition can be obtained that provides a conductive elastic layer that is unlikely to cause C-set even when in contact for a long period of time. According to another aspect of the present disclosure, an electrophotographic member having a conductive elastic layer that is unlikely to cause C-set even when in contact for a long period of time can be obtained. Furthermore, according to another aspect of the present disclosure, a process cartridge that contributes to the stable formation of high-quality electrophotographic images can be obtained. According to yet another aspect of the present disclosure, an electrophotographic image forming apparatus that can stably form high-quality electrophotographic images can be obtained. [Brief description of the drawings]
[0018] [Figure 1] 1 is a schematic cross-sectional view illustrating an example of an electrophotographic member according to the present disclosure. [Diagram 2] FIG. 2 is a schematic cross-sectional view illustrating an example of a process cartridge according to the present disclosure. [Diagram 3] 1 is a schematic configuration diagram illustrating an example of an electrophotographic image forming apparatus according to the present disclosure. [Figure 4] 1 is a schematic diagram of an electric resistance measuring device for an electrophotographic member according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] According to the study by the present inventors, it was estimated that the cause of the occurrence of the C-set in the developing roller according to Patent Document 1 is the carbon black with a low specific surface area contained in the elastic layer of the developing roller according to Patent Document 1. That is, as described in Patent Document 1, carbon black with a low specific surface area, such as carbon black with a DBP absorption amount of 20 ml / 100 g to 50 ml / 100 g, has a low affinity with liquid silicone rubber and is likely to be unevenly distributed on the surface side in the elastic layer. In addition, since the carbon black has a low affinity with liquid silicone rubber, it is considered that the surrounding silicone rubber cannot enter the gaps of the aggregates of the carbon black even in the elastic layer, and minute gaps are present. When a pressing force is applied by contacting such an elastic layer with another member, the silicone rubber is pressed into the gap. It is considered that this state is maintained even after the pressing force is removed, and as a result, the C-set occurs at the contact portion.
[0020] The present inventors recognized that, when using two types of carbon black with different specific surface areas that provide excellent electrical conductivity to the elastic layer, it is necessary to develop a technology to eliminate the gaps between the low specific surface area carbon black aggregates and the silicone rubber in the elastic layer, which is considered to be the cause of C-set. Therefore, as a result of repeated investigations to prevent the occurrence of gaps between the low specific surface area carbon black aggregates and the silicone rubber, they found that the following curable liquid siloxane composition can achieve this purpose well.
[0021] That is, a siloxane composition comprising the following components (A) to (D): (A) an organopolysiloxane consisting of the following components (A-1) and (A-2): (A-1) Organopolysiloxane represented by the following average composition formula (1):
[0022] [ka]
[0023] (In the average composition formula (1), R1 each independently represents an alkyl group having 1 to 10 carbon atoms, R2 each independently represents an alkenyl group having 2 to 8 carbon atoms, and m is a number of 1,000 or more and 2,000 or less.) (A-2) Organopolysiloxane represented by the following average composition formula (2):
[0024] [ka]
[0025] (In the average composition formula (2), R3's each independently represent an alkyl group having 1 to 10 carbon atoms, R4's each independently represent an alkenyl group having 2 to 8 carbon atoms for each repeating unit, о is a number from 10 to 45, and n+о is a number from 300 to 500.) (B) Specific surface area is 60m 2 / g or more 100m 2 A first carbon black having a molecular weight of 1 / g or less; (C) Specific surface area is 12 m 2 / g or more 30m 2 / g or less of a second carbon black; (D) Organohydrogenpolysiloxane represented by the following average composition formula (3):
[0026] [ka]
[0027] (In the average composition formula (3), R5 each independently represents an alkyl group having 1 to 10 carbon atoms, p is a number of 3 or more and 20 or less, and q is a number of 4 or more and 20 or less.) the ratio of the component (A-2) in the component (A) is 0.1% by mass or more and 5.0% by mass or less, a ratio (C2 / C1) of the content C2 of the second carbon black to the content C1 of the first carbon black is 2.0 or more and 25.0 or less; the total amount of the first carbon black and the second carbon black relative to the siloxane composition is 10% by mass or more and 30% by mass or less.
[0028] The present inventors speculate that the reason why the formation of gaps between the silicone rubber and the aggregates of the carbon black, which has a low specific surface area, in the cured product of the above-mentioned siloxane composition can be suppressed and, as a result, the cured product is less likely to undergo C set is as follows.
[0029] The siloxane composition according to one embodiment of the present disclosure described above contains a certain amount of component (A-2) represented by average composition formula (2). This component is an organopolysiloxane having an alkenyl group in the side chain portion (R4) and a trialkylsiloxy group (-OSi(R3)3) at both ends. When a siloxane composition containing such an organopolysiloxane is cured, the alkenyl group of component (A-2) undergoes a hydrosilylation reaction with the hydrosilyl group (SiH) of component (D), which is a crosslinking agent, to form a crosslinking point of the polymer. In addition, in the average composition formula (2), n+о is 300 or more and 500 or less, and in the cured product of the siloxane composition, the crosslinking points caused by the alkenyl group and the trialkylsiloxy groups at both ends are relatively close to each other. Therefore, it is considered that the trialkylsiloxy groups can be present at a high density in the vicinity of the crosslinking points. In addition, since trialkylsiloxy groups are highly hydrophobic, hydrophobic interactions tend to occur with the vicinity of the carbon black surface. That is, in the silicone resin in the cured product, trialkylsiloxy groups with high affinity to carbon black are thought to be present at high density in the vicinity of the crosslinking points derived from the alkenyl groups of component (A-2). As a result, it is thought that the affinity between the silicone resin and carbon black is increased, and the voids in the carbon black aggregates are easily filled with the surrounding silicone rubber. As a result, it is thought that the occurrence of C set is effectively suppressed in the cured product of the siloxane composition according to one embodiment of the present disclosure.
[0030] <Siloxane composition> [(A) Organopolysiloxane composed of components (A-1) and (A-2)] ((A-1) Organopolysiloxane represented by the following average composition formula (1))
[0031] [ka]
[0032] In the average composition formula (1), R1 each independently represents an alkyl group having 1 to 10 carbon atoms. From the viewpoint of suppressing steric hindrance and thereby suppressing plastic deformation due to molecular entanglement, R1 is preferably a linear alkyl group having 1 to 4 carbon atoms, more preferably a methyl group. Note that for multiple m, R1 may be different for each repeating unit ((R1)2SiO). Each R2 independently represents an alkenyl group having 2 to 8 carbon atoms. Examples of R2 include vinyl, allyl, propenyl, isopropenyl, butenyl, isobutenyl, pentenyl, and hexenyl groups. Among these, vinyl is preferred as R2. By having an alkenyl group, which is a reactive functional group, at the end, the distance between crosslinking points after curing becomes almost constant compared to side chains, resulting in a regular molecular structure. Therefore, there is little molecular entanglement, and plastic deformation can be suppressed.
[0033] The average degree of polymerization m of the organopolysiloxane represented by the average composition formula (1) is a number from 1000 to 2000. The average degree of polymerization m is more preferably a number from 1500 to 2000. When the average degree of polymerization m is within the above range, the flexibility required for the elastic layer can be obtained.
[0034] Here, the average degree of polymerization is a value calculated from the weight average molecular weight (Mw) obtained from a measurement using gel permeation chromatography (GPC). Specifically, a high-performance liquid chromatograph analyzer (product name: HLC-8120GPC, Tosoh Corporation) is used, in which two GPC columns (product name: TSKgel SuperHM-m, Tosoh Corporation) are connected in series. The measurement conditions are a temperature of 40°C, a flow rate of 0.6 ml / min, and RI (refractive index), and a tetrahydrofuran (THF) solution containing 0.1 mass% of the measurement sample is prepared and measured. Monodisperse standard polystyrene (product name: TSK standard polystyrene F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500, Tosoh Corporation) is prepared as a standard sample. A calibration curve is prepared using the standard sample. The molecular weight distribution is obtained from the retention time or count number of the measurement sample. The weight average molecular weight Mw is obtained from this molecular weight distribution, and the average degree of polymerization can be calculated.
[0035] Commercially available products can be used as component (A-1). Specific examples of polydimethylsiloxanes having vinyl groups at both ends include the following products: DMS-V41, DMS-V42, DMS-V43, DMS-V46, and DMS-V51 (all trade names, manufactured by Gelest). The (A-1) component can be obtained by a known method. For example, an organocyclopolysiloxane such as dimethylcyclopolysiloxane or methylvinylcyclopolysiloxane and a hexaorganodisiloxane such as hexamethyldisiloxane or 1,3-divinyl-1,1,3,3-tetramethyldisiloxane are used. The (A-1) component can be obtained by carrying out an equilibration reaction using these in the presence of an alkali catalyst or an acid catalyst.
[0036] In this specification, the term "average compositional formula" refers to a compositional formula expressed when, in the case of a mixture of organopolysiloxanes having different structures, the compositions of the multiple organopolysiloxanes constituting the mixture are averaged.
[0037] The (A-1) component may be used alone or in combination of two or more. When the (A-1) component is composed of a mixture of two or more organopolysiloxanes, any organopolysiloxane may be used as long as the average degree of polymerization m of the mixture is 1000 or more and 2000 or less. Specifically, for example, even if R1 and R2 are within the range specified by the average composition formula (1), an organopolysiloxane with an average degree of polymerization m exceeding 2000 (for example, "DMS-V52", product name, manufactured by Gelest Co., Ltd.) can be used as a constituent of the (A-1) component by combining it with another organopolysiloxane to make the average degree of polymerization m 1000 or more and 2000 or less. When the (A-1) component is composed of two or more organopolysiloxanes, the average degree of polymerization m can be calculated by the same method as described above. Specifically, the average degree of polymerization m can be calculated by using a mixture of two or more types of organopolysiloxane as the measurement sample.
[0038] ((A-2) Organopolysiloxane represented by the following average composition formula (2))
[0039] [ka]
[0040] In the average composition formula (2), R3 each independently represents an alkyl group having 1 to 10 carbon atoms. R3 is preferably a linear alkyl group having 1 to 4 carbon atoms, more preferably a methyl group. For multiple n's, R3 may be different for each repeating unit ((R3)2SiO). For multiple o's, R3 may be different for each repeating unit (R3R4SiO). R4 independently represents an alkenyl group having 2 to 8 carbon atoms for each repeating unit. Examples of R4 include vinyl, allyl, propenyl, isopropenyl, butenyl, isobutenyl, pentenyl, and hexenyl groups. Among these, vinyl is preferred as R4. By having an alkenyl group, which is a reactive functional group, in a side chain, the distance between crosslinking points after curing becomes shorter compared to the terminal, and the terminal trialkylsiloxy groups tend to be more easily clustered.
[0041] The average degree of polymerization n+о of the organopolysiloxane represented by the average composition formula (2) is a number between 300 and 500. When n+о is within the above range, the terminal trialkylsiloxy groups can be concentrated near the crosslinking points. Among them, о is a number between 10 and 45. When о is 10 or more, the distance between the crosslinking points can be made closer, so that the terminal trialkylsiloxy groups can be fixed so as not to move more than necessary. In addition, when о is 45 or less, the distance between the crosslinking points does not become too short, so that flexibility can be maintained, and plastic deformation can be suppressed. In particular, when о is a number between 15 and 25, the degree of freedom of the terminal trialkylsiloxy groups is high, and they can easily approach the carbon black, which is more preferable. Here, the average degrees of polymerization n and o are 1 It is a value calculated from the integral ratio of the integral value of the peak derived from the alkenyl group obtained from H-NMR to the integral value of the peak derived from the alkyl group bonded to the silicon atom, and the weight average molecular weight (Mw) obtained from the GPC.
[0042] Commercially available products can be used as component (A-2). Specific examples of dimethylsiloxane-methylvinylsiloxane copolymers terminated at both ends with trimethylsiloxy groups include the following products: VDT-431, VDT-731 (both trade names, manufactured by Gelest Co., Ltd.), etc.
[0043] The ratio of component (A-2) in component (A) is 0.1% by mass or more and 5.0% by mass or less. By making the ratio of component (A-2) 0.1% by mass or more, a certain amount of crosslinking points in the vicinity of which trialkylsiloxy groups are present at a high density can be introduced into the molecular structure of the silicone resin. In addition, by making the ratio of component (A-2) 5.0% by mass or less, the terminal trialkylsiloxy groups are not present in excess, and the deterioration of plastic deformation due to molecular entanglement can be suppressed.
[0044] The component (A-2) may be used alone or in combination of two or more. When the component (A-2) is composed of a mixture of two or more organopolysiloxanes, any organopolysiloxane may be used for each of the organopolysiloxanes as long as the average degree of polymerization of the mixture, o, is a number between 10 and 45, and n+o is a number between 300 and 500. When the component (A-2) is composed of two or more organopolysiloxanes, the average degree of polymerization, n+o, can be calculated by the same method as described above.
[0045] [(B) first carbon black, (C) second carbon black] The first carbon black has a specific surface area of 60 m 2 / g or more 100m 2 / g or less, and the second carbon black has a specific surface area of 12 m 2 / g or more 30m 2 / g or less, more preferably 20m 2 / g or more 30m 2 / g or less. When the specific surface area of the first carbon black is within the above range, the elastic layer as a whole can have conductive characteristics in the medium resistance region. Here, the medium resistance region is, in terms of electrical resistivity, 1.0×10 -9 Ω cm or more 1.0×10 -6 It is preferable that the specific surface area of the second carbon black is Ω·cm or less. In addition, since the specific surface area of the second carbon black is within the above range, the carbon black can be present in the vicinity of the surface of the elastic layer, so that the surface potential of the elastic layer can be reduced.
[0046] Here, the specific surface area refers to the nitrogen specific surface area (NSA) based on the multipoint method of BET gas adsorption theory, as defined in the Japanese Industrial Standards (JIS) K6217-7:2013 "Carbon black for rubber - Basic properties - Part 7: Rubber compounds - Determination of multipoint nitrogen specific surface area (NSA) and statistical thickness specific surface area (STSA)". As described in the standard, this is a method for measuring the total specific surface area including the pores of carbon black, which is inversely proportional to the primary particle size. Generally, the more voids there are in carbon black, the more nitrogen is adsorbed and the larger the specific surface area tends to be.
[0047] The first and second carbon blacks may be commercially available. Specifically, examples of the first carbon black include Asahi #70, Asahi #70L, SUNBLACK735, SUNBLACK200, SUNBLACK280, SUNBLACK285, SUNBLACK335, SUNBLACK605, and SUNBLACK X55 (all trade names, manufactured by Asahi Carbon Co., Ltd.); Denka Black powder, Denka Black 100% pressed, Denka Black granular, and Denka Black Li-100 (all trade names, manufactured by Denka Co., Ltd.); Seast 5H, Seast KH, Seast 3H, Seast NH, Seast 3, Seast N, and Seast 300 (all trade names, manufactured by Tokai Carbon Co., Ltd.); and #52, #33, #32, #30, #85, #24, MA11, MA230, and #4000B (all trade names, manufactured by Mitsubishi Carbon Co., Ltd.). Examples of the second carbon black include Asahi #55, Asahi #50HG, Asahi #52, Asahi #50, Asahi #50U, Asahi #35, Asahi #22K, Asahi #15HS, Asahi #15, Asahi #8, Asahi Thermal, SUNBLACK 235, SUNBLACK 250 (all trade names, manufactured by Asahi Carbon Co., Ltd.); Seest V, Seest FY, Seest S, Seest SP, Seest TA (all trade names, manufactured by Tokai Carbon Co., Ltd.). Carbon black whose specific surface area has been adjusted by various surface treatments can also be used.
[0048] The content of the second carbon black is preferably 11% by mass or more and 15% by mass or less based on the siloxane composition. By having the content of the second carbon black within the above range, it is possible to suppress voids while maintaining a low surface potential, and therefore to further suppress plastic deformation.
[0049] The ratio (C2 / C1) of the second carbon black content C2 to the first carbon black content C1 is 2.0 or more and 25.0 or less. By having C2 / C1 within the above range, it is possible to suppress voids between the siloxane and the carbon black. In particular, when C2 / C1 is 5.0 or more and 10.0 or less, it is possible to suppress voids while maintaining a low surface potential, and therefore it is possible to further suppress plastic deformation.
[0050] The total amount of carbon black relative to the siloxane composition, i.e., the total amount of the first carbon black and the second carbon black, is 10% by mass to 30% by mass, and preferably 10% by mass to 20% by mass. By having the total amount of the first carbon black and the second carbon black within the above range, it is possible to suppress plastic deformation by maintaining rubber elasticity while making the elastic layer conductive in the medium resistance range.
[0051] The method for measuring the specific surface area of carbon black and the carbon black content ratio C2 / C1 from the siloxane composition of the present disclosure will be exemplified below. The siloxane composition is diluted with an organic solvent such as xylene, and ultrasonically irradiated to separate the siloxane component and the carbon black. After standing, the precipitated carbon black is collected, diluted with an ethanol solution, and classified using an ultracentrifuge (such as that manufactured by Eppendorf-Himack Technologies) that utilizes the density gradient sedimentation velocity method. The separated carbon black is collected and dried, and then the specific surface area is measured according to the above-mentioned JIS K6217-7:2013. In addition, the ratio C2 / C1 of the carbon black content can be derived by measuring the mass of the separated carbon black. The total amount of carbon black can be derived by measuring the siloxane composition using known thermogravimetric analysis.
[0052] [(D) Organohydrogenpolysiloxane represented by the following average composition formula (3)]
[0053] [ka]
[0054] In the average composition formula (3), R5 each independently represents an alkyl group having 1 to 10 carbon atoms. R5 is preferably a linear alkyl group having 1 to 4 carbon atoms, more preferably a methyl group. For multiple p's, R5 may be different for each repeating unit ((R5)2SiO). For multiple q's, R5 may be different for each repeating unit (R5HSiO).
[0055] The average degree of polymerization p is a number between 3 and 20, and q is a number between 4 and 20. When the average degrees of polymerization p and q are within the above ranges, the terminal trialkylsiloxy groups can be concentrated near the crosslinking points. In addition, when p and q are within the above ranges, the elastic layer can be given the necessary flexibility. Here, the average degrees of polymerization p and q are 1 It is a value calculated from the integral ratio of the integral value of the peak derived from hydrogen atoms bonded to silicon atoms obtained from H-NMR to the integral value of the peak derived from alkyl groups bonded to silicon atoms, and the weight average molecular weight (Mw) obtained from the GPC.
[0056] The organohydrogenpolysiloxane, which is component (D), is a crosslinking agent used in the addition curing reaction with the organopolysiloxane consisting of components (A-1) and (A-2). For example, the following can be given as component (D): a dimethylsiloxane-methylhydrogensiloxane copolymer terminated at both ends of the molecular chain with trimethylsiloxy groups, a mixture of two or more of such copolymers, and a mixture of such a copolymer and a polymethylhydrogensiloxane terminated at both ends of the molecular chain with trimethylsiloxy groups. The component (D) may be used alone or in combination of two or more. When the component (D) is composed of a mixture of two or more organohydrogenpolysiloxanes, any organohydrogenpolysiloxane may be used as long as the average polymerization degrees p and q of the mixture are as described above. Specifically, for example, the polymethylhydrogensiloxane capped at both ends of the molecular chain with trimethylsiloxy groups is an organohydrogenpolysiloxane in which p in the average composition formula (3) is 0, and does not satisfy the average composition formula (3) by itself. However, when used in combination with another dimethylsiloxane-methylhydrogensiloxane copolymer capped at both ends of the molecular chain with trimethylsiloxy groups, it can be used as a component (D) that satisfies the average composition formula (3).
[0057] Commercially available products can be used as component (D), including, for example, HMS-151, HMS-301, and HMS-501 (all trade names, manufactured by Gelest), which are dimethylsiloxane-methylhydrogensiloxane copolymers terminated at both ends with trimethylsilyl groups.
[0058] The content of the (D) component in the silicone composition is preferably such that the molar ratio of hydrogen atoms bonded to silicon atoms in the (D) component to alkenyl groups bonded to silicon atoms contained in the organopolysiloxane consisting of the (A-1) and (A-2) components is 1.0 or more and 6.0 or less. The molar ratio is more preferably 1.0 or more and 5.0 or less. By keeping the molar ratio within the above range, unreacted materials can be suppressed, and the viscous components can be reduced to further suppress plastic deformation.
[0059] [Catalytic compound] The catalyst compound is a catalyst used to promote the addition curing reaction between the components (A-1) and (A-2) and the component (D). Examples of the catalyst compound include the following: platinum fine powder, platinum black, chloroplatinic acid, alcohol-modified chloroplatinic acid, olefin complexes of chloroplatinic acid, and complexes of platinum and alkenylsiloxane. Commercially available catalyst compounds can be used, and specific examples include SIP6829.2, SIP6832.2, SIP6830.3, SIP6831.2, and SIP6833.2 (all trade names, manufactured by Gelest Co., Ltd.). These may be used alone or in combination of two or more. The content of the catalyst compound in the siloxane composition is preferably an amount of 1 ppm by mass or more and 100 ppm by mass or less, from the viewpoint of curing reactivity.
[0060] [Other ingredients] In addition to the above, the siloxane composition according to the present disclosure may contain various additives, such as a reinforcing agent, a cure regulator, a conductive agent, a plasticizer, a vulcanizing agent, a vulcanization aid, a crosslinking aid, an antioxidant, an antiaging agent, and a processing aid, as necessary, to the extent that the functions of the composition are not impaired.
[0061] [Method of Preparing Siloxane Composition] The siloxane composition according to the present disclosure can be prepared by mixing the above-mentioned components using a known mixing device. Examples of the mixing device include the following devices. For example, dynamic mixing devices such as a single screw extruder, a twin screw extruder, a kneader mixer, a two-roll mill, a three-roll mill, a Banbury mixer, a continuous mixer, a planetary mixer, a three-screw mixer, and a rotation-revolution mixer, and static mixing devices such as a static mixer are included. In particular, when the wettability of the organosiloxane such as component (A-1) with the carbon black is low and dispersion is difficult, it is preferable to use a dispersion method based on so-called "stiff kneading" as described in JP-A-2005-113031. "Stiff kneading" increases the viscosity of the dispersion, thereby increasing the shear stress and enabling the carbon black aggregates to be broken down.
[0062] <Electrophotographic materials> The electrophotographic member according to the present disclosure has a substrate and an elastic layer on the substrate, and the elastic layer is formed from a cured product of the siloxane composition according to the present disclosure. A representative example of the electrophotographic member is a conductive roller used in an electrophotographic image forming apparatus. Examples of the conductive roller include a charging roller, a developing roller, and a transfer roller. Hereinafter, the electrophotographic member according to the present disclosure will be described using a representative example of a developing roller, but the present disclosure is not limited thereto.
[0063] The electrophotographic member of the present disclosure can be applied to any of non-contact type developing devices and contact type developing devices using a magnetic one-component developer or a non-magnetic one-component developer, and developing devices using a two-component developer. As an example of the electrophotographic member of the present disclosure, a developing roller is shown in Figs. 1(a) and 1(b). The electrophotographic member 1 shown in Fig. 1(a) is composed of a base body 2 and an elastic layer 3 provided on the outer periphery thereof. As shown in Fig. 1(b), the electrophotographic member 1 may be provided with the base body 2, the elastic layer 3, and a surface layer 4 as required.
[0064] [Base] The substrate 2 is not particularly limited, and may be hollow or solid. The substrate 2 has a conductive outer surface and has a function of supporting the elastic layer 3 provided thereon. Examples of the material include metals such as iron, copper, aluminum, and nickel; and alloys containing these metals such as stainless steel, duralumin, brass, bronze, and free-cutting steel. The outer surface of the conductive substrate may be plated with chromium or nickel to the extent that the conductivity is not impaired. Furthermore, as the conductive substrate, a substrate made of a resin whose surface is coated with a metal to make the surface conductive, or a substrate made of a conductive resin composition may also be used. A known adhesive may be applied to the surface of the conductive substrate 2 in order to improve the adhesion with the elastic layer 3 provided on the outer peripheral surface of the substrate. The size of the substrate 2 is not particularly limited, and may be, for example, an outer diameter of 4 mm or more and 20 mm or less and a length of 200 mm or more and 380 mm or less.
[0065] [Elastic layer] An elastic layer 3 made of a cured product of the siloxane composition according to the present disclosure is formed on the outer periphery of the substrate 2. The elastic layer has the elasticity required for electrophotographic members, and is provided directly or indirectly on the outer peripheral surface of the substrate. The hardness of the elastic layer can be, for example, 20 degrees or more and 80 degrees or less in terms of Asker C hardness. The thickness of the elastic layer can be, for example, 0.3 mm or more and 6.0 mm or less. The thickness of the elastic layer can be determined by observing and measuring the cross section with an optical microscope. Methods for forming the elastic layer on the substrate include molding, extrusion, injection molding, coating molding, and the like.
[0066] [Surface layer] Examples of the material of the surface layer 4 include the following: Thermoplastic resins such as styrene resins, vinyl resins, polyethersulfone resins, polycarbonate resins, polyphenylene oxide resins, polyamide resins, fluororesins, cellulose resins, and acrylic resins; epoxy resins, polyester resins, alkyd resins, phenolic resins, melamine resins, benzoguanamine resins, polyurethane resins, urea resins, silicone resins, polyimide resins, photocurable resins, and the like. When the electrophotographic member according to the present disclosure is used as a developing roller, polyurethane resins are particularly preferred because of their excellent ability to provide triboelectric charging to toner. These resins may be used alone or in combination of two or more.
[0067] When surface roughness is required, roughness-controlling fine particles can be contained in the surface layer 4. The volume average particle diameter of the roughness-controlling fine particles is preferably 3 μm or more and 20 μm or less. The amount of the fine particles contained in the surface layer 4 is preferably 1 part by mass or more and 50 parts by mass or less per 100 parts by mass of the resin component. As the roughness-controlling fine particles, fine particles of polyurethane resin, polyester resin, polyether resin, polyamide resin, acrylic resin, polycarbonate resin, etc. can be used.
[0068] By blending a conductivity imparting agent such as an electronically conductive substance or an ionically conductive substance with the various resins, the surface layer 4 can be imparted with conductivity and adjusted to an appropriate resistance range. Examples of electronically conductive substances include the following: conductive carbon black such as Ketjen Black EC and acetylene black; rubber carbon black such as SAF, ISAF, HAF, FEF, GPF, SRF, FT, and MT; color (ink) carbon black that has been subjected to oxidation treatment; and metals and metal oxides such as copper, silver, and germanium. Among these, conductive carbon black is preferred because it is easy to control the conductivity with a small amount. The content of conductive carbon black in the surface layer 4 is preferably 3% by mass or more and 30% by mass or less with respect to the resin components. These electronically conductive substances may be used alone or in combination of two or more types. Examples of the ion-conductive substance include the following: inorganic ion-conductive substances such as sodium perchlorate, lithium perchlorate, calcium perchlorate, and lithium chloride; and organic ion-conductive substances such as modified aliphatic dimethylammonium ethosulfate and stearyl ammonium acetate. The content of the ion-conductive substance in the surface layer 4 is preferably 0.1% by mass or more and 20% by mass or less with respect to the resin component. These ion-conductive substances may be used alone or in combination of two or more kinds.
[0069] In addition to the above, the surface layer 4 may contain a crosslinking agent, a plasticizer, a filler, an extender, a vulcanizing agent, a vulcanization aid, a crosslinking aid, an antioxidant, an antiaging agent, a processing aid, a leveling agent, etc., within the range not impairing the function.
[0070] The thickness of the surface layer 4 is preferably 1 μm or more and 100 μm or less. By making the thickness of the surface layer 1 μm or more, deterioration due to wear and the like can be suppressed. In addition, by making the thickness of the surface layer 100 μm or less, it is possible to suppress the surface of the electrophotographic member from becoming too hard, suppress toner deterioration, and suppress toner-derived adhesion to the surface of the electrophotographic member. In consideration of damage to the toner, it is more preferable that the thickness of the surface layer is 1 μm or more and 50 μm or less.
[0071] The method for forming the surface layer 4 is not particularly limited, but for example, each component of the surface layer 4 is dispersed and mixed in a solvent to form a paint, and a coating liquid for forming the surface layer is prepared. The coating liquid for forming the surface layer is applied onto the elastic layer 3, and then dried and solidified or cured to form the surface layer 4. For dispersion and mixing, it is preferable to use a known dispersing device using beads such as a sand mill, a paint shaker, a dyno mill, or a pearl mill. As a coating method, dip coating, ring coating, spray coating, roll coating, or the like can be adopted.
[0072] <Process cartridge> The process cartridge according to the present disclosure includes the electrophotographic member according to the present disclosure and is configured to be detachably attached to the main body of the electrophotographic image forming apparatus. FIG. 2 shows an example of the process cartridge according to the present disclosure using the electrophotographic member according to the present disclosure as a developing roller 1. The process cartridge shown in FIG. 2 has a developing device 10 including a developing roller 1 and a developing blade 9, an electrophotographic photoreceptor 5, a cleaning blade 6, a waste toner storage container 13, and a charging roller 12, which are integrated and detachably provided in the main body of the electrophotographic image forming apparatus. The developing device 10 further includes a toner container filled with toner 8. The toner 8 is supplied to the surface of the developing roller 1 by a toner supply roller 7, and a layer of the toner 8 having a predetermined thickness is formed on the surface of the developing roller 1 by the developing blade 9. In addition to the above, the process cartridge according to the present disclosure may be one in which a transfer member for transferring a toner image on the electrophotographic photoreceptor 5 to a recording material and the like are integrally provided together with the above members. Also, the process cartridge according to the present disclosure may be configured so that only the developing device 10 is detachable.
[0073] <Electrophotographic image forming apparatus> The electrophotographic image forming apparatus according to the present disclosure includes an image carrier for carrying an electrostatic latent image, a charging device for primarily charging the image carrier, an exposure device for forming an electrostatic latent image on the primarily charged image carrier, a developing device for developing the electrostatic latent image with toner to form a toner image, and a transfer device for transferring the toner image to a transfer material. The developing device includes the electrophotographic member according to the present disclosure. FIG. 3 is a schematic cross-sectional view showing an example of an electrophotographic image forming apparatus equipped with an electrophotographic member according to the present disclosure as a developing roller of a contact developing device using one-component toner. In this electrophotographic image forming apparatus, a charging member (charging roller) 12 that charges the surface of the electrophotographic photoreceptor 5 to a predetermined polarity and potential is arranged around the electrophotographic photoreceptor 5 rotated by a rotating mechanism (not shown). Furthermore, an image exposure device (not shown) that performs image exposure on the charged surface of the electrophotographic photoreceptor 5 to form an electrostatic latent image is arranged. Furthermore, a developing device 10 including a developing roller 1 according to the present disclosure that develops the formed electrostatic latent image by attaching toner 8 to the electrostatic latent image is arranged around the electrophotographic photoreceptor 5. Furthermore, a cleaning device 13 that cleans the electrophotographic photoreceptor 5 after transferring a toner image to paper 22 is provided. A fixing device 15 that fixes the transferred toner image on the paper 22 is arranged on the transport path of the paper 22.
[0074] The print operation of the electrophotographic image forming apparatus will be described below. The electrophotographic photoreceptor 5 rotates in the direction of the arrow, and is uniformly charged by a charging roller 12 for charging the electrophotographic photoreceptor 5. Then, an electrostatic latent image is formed on the surface of the electrophotographic photoreceptor 5 by a laser beam 11, which is an exposure means. The electrostatic latent image is visualized as a toner image (developed) by applying toner 8 supplied from a toner supply roller 7 to the electrostatic latent image from a developing roller 1 arranged in contact with the electrophotographic photoreceptor 5. The development is a so-called reversal development in which a toner image is formed in the exposed portion. The toner image formed on the electrophotographic photoreceptor 5 is transferred to a recording medium, paper 22, by a transfer roller 17, which is a transfer member. Note that a voltage is applied to the transfer roller 17 from a bias power source 18. The paper 22 is fed into the apparatus via a paper feed roller 23 and an adsorption roller 24, and is transported between the electrophotographic photoreceptor 5 and the transfer roller 17 by an endless belt-like transfer transport belt 20. The transfer and transport belt 20 is operated by a driven roller 21, a drive roller 16, and a tension roller 19. The paper 22 onto which the toner image has been transferred is peeled off from the transfer and transport belt 20 by a peeling device 14, and sent to a fixing device 15. Then, after being subjected to a fixing process by the fixing device 15, the paper is discharged outside the device, and the printing operation is completed. Meanwhile, residual toner remaining on the electrophotographic photoreceptor 5 without being transferred is scraped off by a cleaning blade 6, which is a cleaning member for cleaning the surface of the electrophotographic photoreceptor, and is stored in a waste toner storage container 13. The cleaned electrophotographic photoreceptor 5 repeats the above printing operation. EXAMPLES
[0075] The present disclosure will be described below with reference to specific production examples, examples, and comparative examples, but the present disclosure is not limited thereto.
[0076] <Carbon black> The carbon black used was a commercially available carbon black shown in Table 1. The specific surface area measured in accordance with JIS K6217-7:2013 is shown in Table 1.
[0077] [Table 1]
[0078] <Production Example of Siloxane Composition 1 According to Example 1> The raw materials shown in Table 2 were charged into a planetary mixer (product name: PLM-2, manufactured by Inoue Manufacturing Co., Ltd.) and dispersed for 1 hour at a rotation speed of 60 rpm / revolution of 19 rpm to prepare a siloxane-carbon black dispersion intermediate. Then, an additional 60 parts by mass (total of 100 parts by mass) of component (A-1) shown in Table 2 was added and dispersed for 2 hours to obtain a siloxane-carbon black dispersion.
[0079] [Table 2]
[0080] The siloxane-carbon black dispersion and the raw materials shown in Table 3 were charged into a centrifugal mixer (product name: ARE-500, manufactured by Thinky Corporation) and dispersed at a rotation speed of 2000 rpm for 3 minutes to produce Siloxane Composition 1. The average degrees of polymerization of components (A-1), (A-2) and (D) were m=1700, n=370, о=20, p=20 and q=10, respectively.
[0081] [Table 3]
[0082] <Production Examples of Siloxane Compositions 2 to 37 According to Examples 2 to 19 and Comparative Examples 1 to 18> <Production Examples of Siloxane Compositions 2-18 and 20-36> Siloxane compositions 2 to 18 and 20 to 36 were produced in the same manner as siloxane composition 1, except that the types and amounts of components (A-1), (A-2), (B), and (C) were changed as shown in Tables 4-1 and 4-2, respectively.
[0083] [Table 4-1]
[0084] [Table 4-2]
[0085] <Production Example of Siloxane Composition 19> Siloxane composition 19 was produced in the same manner as siloxane composition 1, except that the two types of organopolysiloxane shown in Table 5 were used as component (A-1). The average degree of polymerization m of component (A-1) was 1,100.
[0086] [Table 5]
[0087] <Production Example of Siloxane Composition 37> The raw materials shown in Table 6 were charged into a planetary centrifugal mixer (product name: ARE-500, manufactured by Thinky Corporation) and dispersed at a rotation speed of 2000 rpm for 3 minutes to produce Siloxane Composition 37. The average degree of polymerization m of component (A-1) was 1200. The average degrees of polymerization of components (A-2) and (D) were n=370, о=20, p=7, and q=7, respectively.
[0088] [Table 6]
[0089] Example 1 <Manufacture of Electrophotographic Member 1> [Preparation of the substrate] A SUS304 substrate with an outer diameter of 6 mm and a length of 250 mm was coated with a primer paint made by mixing 100 parts by mass of primer (product name: DY39-051, manufactured by DuPont Toray Specialty Materials) and 5 parts by mass of additive (product name: VDT-431, manufactured by Gelest Corporation), and baked at 170°C for 20 minutes.
[0090] [Formation of elastic layer] The prepared substrate was placed concentrically in a cylindrical mold having an inner diameter of 12 mm. The siloxane composition 1 obtained above was poured into the mold. After heating and molding at 115°C for 5 minutes, the mold was cooled to 50°C, and the elastic layer integrated with the substrate was removed from the mold. As a result, an elastic layer having a diameter of 12 mm was provided on the outer periphery of the substrate.
[0091] [Measurement of surface potential] A dielectric relaxation analyzer (product name: DRA-2000L, manufactured by Quality Engineering Associates, Inc.) was used to measure the surface potential of the member provided with the elastic layer. This device is composed of a scanner and a non-contact electrostatic potential meter, and can measure the surface potential at any position on the surface of the member provided with the elastic layer by scanning a carriage containing a corona charger and an electrostatic probe in the axial direction. The surface potential measured here refers to the residual potential of the surface of the member measured by the probe located behind the charger in the direction of travel after charging with the charger. The measurements were performed at 240 points at 1 mm intervals in the longitudinal direction of the surface layer and 36 points at 10° intervals in the circumferential direction, for a total of 8640 points. The distance between the surface layer and the probe was 0.76 mm, the carriage scanning speed was 400 mm / sec, and the voltage applied to the corona charger was 6 kV. The arithmetic mean value of the 8640 points was taken as the surface potential. The evaluation results obtained are shown in Table 11.
[0092] [Formation of surface layer] (Synthesis of surface layer raw materials) (Synthesis of polyurethane polyol) 100.0 parts by mass of polytetramethylene glycol (product name: PTG1000SN, manufactured by Hodogaya Chemical Co., Ltd.) was mixed in stages with 28.2 parts by mass of an isocyanate compound (product name: Cosmonate MDI, manufactured by Mitsui Chemicals, Inc.) in a methyl ethyl ketone (MEK) solvent, and the mixture was allowed to react for 3 hours at a temperature of 80°C under a nitrogen atmosphere to obtain a polyurethane polyol having a weight average molecular weight Mw=9000 and a hydroxyl value of 22.
[0093] (Synthesis of isocyanate-terminated prepolymer) Under a nitrogen atmosphere, 100.0 parts by mass of polypropylene glycol polyol (product name: Sannix PP-1000, manufactured by Sanyo Chemical Industries Co., Ltd.) was gradually added dropwise to 73.5 parts by mass of pure-MDI (product name: Millionate MT, manufactured by Nippon Polyurethane Industry Co., Ltd.) in a reaction vessel while maintaining the temperature in the reaction vessel at 65° C. After completion of the dropwise addition, the mixture was reacted at a temperature of 65° C. for 2.5 hours. The resulting reaction mixture was cooled to room temperature to obtain an isocyanate-terminated prepolymer having an isocyanate group content of 5.1% by mass.
[0094] (Formation of surface layer) As the material for the surface layer, the materials shown in Table 7 were mixed and stirred.
[0095] [Table 7]
[0096] Next, methyl ethyl ketone was added so that the total solids ratio was 30% by mass, and then mixed in a sand mill. Next, the viscosity was further adjusted to 10 to 12 cps (mPa s) with methyl ethyl ketone to prepare the coating material for forming the surface layer. The elastic layer provided on the outer periphery of the substrate was immersed in the coating material for forming the surface layer, and the coating material was formed on the surface of the elastic layer, followed by drying. Further, a surface layer having a thickness of about 15 μm was provided on the outer periphery of the elastic layer by heat treatment at a temperature of 150° C. for 1 hour, thereby producing an electrophotographic member 1 according to Example 1.
[0097] [Evaluation 1: Measurement of electrical resistivity] The obtained electrophotographic member 1 was left to stand for 24 hours in an environment of a temperature of 23° C. and a humidity of 55% RH, and the electrical resistivity was determined by the measurement method shown below. A schematic diagram of the electrical resistance measuring device for electrophotographic members is shown in FIG. 4. A load F of 4.9 N was applied to both ends of the substrate 2 of the electrophotographic member 1, and the electrophotographic member 1 was pressed against a metal drum 25 having an outer diameter of 30 mm. Then, while the electrophotographic member 1 was rotated by the roller of the metal drum 25 at a rotation speed of 1 rps, a voltage of 50 V was applied to the electrophotographic member 1 by a power source 26. At this time, the voltage applied to the internal resistance 28 (1 kΩ) indicated by a voltmeter 27 was recorded at 3000 points for 30 seconds, and the arithmetic mean value was calculated. From the obtained values, the electrical resistivity of the electrophotographic member 1 was calculated according to Ohm's law. The obtained evaluation results are shown in Table 11.
[0098] [Evaluation 2: Evaluation of unevenness in shading] The unevenness in shading was evaluated by the following method. A process cartridge shown in FIG. 2 (product name: EP-85 toner cartridge (black), manufactured by Canon Inc.) was prepared. In this process cartridge, the electrophotographic member 1 according to Example 1 was loaded as a developing roller, and the process cartridge was left for 24 hours or more under an environment of a temperature of 10° C. and a humidity of 10% RH. In the same environment, the process cartridge after aging was assembled into an electrophotographic image forming apparatus (product name: LBP5500, manufactured by Canon Inc.) having a configuration shown in FIG. 3. Thereafter, 10 sheets of a uniform halftone image with an average image density of 0.6 were printed on thick paper (product name: CS-814 A4, manufactured by Canon Inc.). Here, the average image density was determined as follows. The obtained image was divided into 5 cm x 5 cm regions starting from the top left, and the density at the center of each region was measured using a reflection densitometer (product name: X-Rite504, manufactured by X-Rite). The right and bottom parts of the image less than 5 cm in size were not measured. The value obtained by arithmetically averaging the measurements in each region was used as the average image density of the image. In the evaluation images, the halftone image of the tenth sheet was evaluated for unevenness in shading according to the criteria shown in Table 8. The evaluation results are shown in Table 11.
[0099] [Table 8]
[0100] [Evaluation 3: Leak evaluation] A total of 10 halftone images obtained in the evaluation of the above-mentioned unevenness in shading were visually evaluated for leakage according to the criteria shown in the following Table 9. The obtained evaluation results are shown in Table 11.
[0101] [Table 9]
[0102] [Evaluation 4: Measurement of deformation amount and evaluation of horizontal streaks] The electrophotographic member 1 was attached as a developing roller to the developing container of the above-mentioned process cartridge, and the electrophotographic member 1 and the toner amount control member were left standing for one month in an environment of 40°C and 95% RH relative humidity. The contact pressure between the electrophotographic member 1 and the toner amount control member was adjusted to 0.6 N / cm, which was changed to a stricter setting for the C set. Thereafter, the electrophotographic member 1 was left standing for two hours in an environment of 23°C and 55% RH relative humidity. This was loaded into the electrophotographic image forming apparatus, a halftone image was output, and horizontal streaks were visually evaluated according to the criteria in Table 10 below. In addition, the electrophotographic member 1 was taken out from the process cartridge that was evaluated, and left standing for two hours in an environment of 23°C and 55% RH relative humidity, and then the deformation amount (μm) of the surface of the electrophotographic member 1 was measured. The deformation amount of the surface of the electrophotographic member 1 was measured using a laser displacement sensor (product name: LT-9500V, manufactured by Keyence Corporation). A laser displacement sensor was placed perpendicular to the surface of the electrophotographic member 1 from which the toner had been removed by air blowing, and the electrophotographic member 1 was rotated at an arbitrary rotation speed to read the circumferential displacement of the surface of the electrophotographic member 1 and measure the amount of deformation. Measurements were taken at five points at 43 mm pitch in the longitudinal direction, and the average value of the five points was taken as the amount of deformation. The obtained evaluation results are shown in Table 11.
[0103] [Table 10]
[0104] [Examples 2 to 19, Comparative Examples 1 to 18] Electrophotographic members 2 to 19 and C1 to C18 according to Examples 2 to 19 and Comparative Examples 1 to 18 were produced in the same manner as in Example 1, except that siloxane composition 1 was changed to siloxane compositions 2 to 37. For the obtained electrophotographic members 2 to 19 and C1 to C18, the electrical resistivity, the leak image, the surface potential, the image of uneven shading, the amount of deformation, and the image of horizontal stripes were measured and evaluated in the same manner as in Example 1. The measurement and evaluation results are shown in Table 11.
[0105] [Table 11]
[0106] The siloxane compositions used in Examples 1 to 19 each contained a first and second carbon black having a specific surface area of 60 m 2 / g or more 100m 2 / g or less, 12m 2 / g or more 30m 2 / g or less. In addition, the average degree of polymerization of component (A-2), о, is a number between 10 and 45, and n+о is a number between 300 and 500, making it easy to fill the gap between the siloxane and carbon black, suppressing C-set and producing good results.
[0107] In particular, the siloxane composition 1 used in Example 1 has a specific surface area of 20 to 30 m 2 / g, which tends to fill the gap between the siloxane and the carbon black more easily than in Examples 8 and 15, which used siloxane compositions containing second carbon black with a specific surface area outside that range, and is therefore excellent at suppressing C-set. The siloxane composition 1 used in Example 1 contains the second carbon black in an amount ranging from 11 to 15% by mass. This allows the number of gaps between the siloxane and the carbon black to be reduced, and is therefore superior in suppressing C-set, compared to Examples 2 and 16 to 18, which use siloxane compositions with a second carbon black content outside that range. Furthermore, the siloxane composition 1 used in Example 1 has an average degree of polymerization о of the component (A-2) of 15 or more and 25 or less. Therefore, unreacted functional groups can be suppressed more effectively than in Example 14, which uses siloxane composition 14 in which the average degree of polymerization о of the component (A-2) is outside that range, and therefore the suppression of the C set is superior. In addition, the siloxane composition 1 used in Example 1 has a C2 / C1 ratio in the range of 5.0 to 10.0. Therefore, the electrical properties are better balanced and the evaluation results of the surface potential and the unevenness in shading are superior to those of Examples 3 and 5, which used siloxane compositions with a C2 / C1 ratio outside that range. The siloxane composition 1 used in Example 1 was formulated so that the total amount of carbon black was within the range of 10 to 20 mass %. Therefore, the amount of carbon black, which acts as a filler component that reduces rubber elasticity, was less than in Examples 2 and 18, which used siloxane compositions with total amounts of carbon black outside that range, and the suppression of C-set was excellent. In the siloxane composition 1 used in Example 1, R1 is a methyl group in the (A-1) component. Therefore, the steric hindrance of the molecule can be suppressed more than in Example 19, which uses the siloxane composition 19 containing the (A-1) component in which R1 is not a methyl group, and the terminal trialkylsiloxy group is more likely to generate hydrophobic interactions with the carbon black surface. Therefore, the suppression of the C set is excellent.
[0108] On the other hand, the siloxane compositions used in Comparative Examples 1 to 3 had average degrees of polymerization n and o outside the range of the present disclosure, and therefore the amount of terminal trialkylsiloxy groups was inappropriate, and the occurrence of horizontal streaks due to the C set was confirmed. In addition, the siloxane compositions used in Comparative Examples 4 to 6 had an (A-2) component content outside the range of the present disclosure, and therefore the effect of reducing gaps due to the terminal trialkylsiloxy group was weak. As a result, the occurrence of horizontal streaks due to the C set was confirmed. In addition, the siloxane compositions used in Comparative Examples 7 to 15 had carbon black specific surface areas and carbon black contents outside the ranges of the present disclosure, which were inappropriate, resulting in poor balance between electrical properties and suppression of C-set, and poor evaluations of leakage, uneven shading, and horizontal streaks. In addition, the average degree of polymerization m of the component (A-1) in the siloxane compositions used in Comparative Examples 16 and 17 was outside the range of the present disclosure, and therefore the flexibility of the rubber and the entanglement of the molecules were not adequate, and the occurrence of lateral streaks due to the C set was confirmed. Furthermore, the siloxane composition used in Comparative Example 18 had a carbon black content outside the range of the present disclosure, and therefore the occurrence of horizontal streaks due to the C set was confirmed. [Explanation of symbols]
[0109] 1: Developing roller 2: Base 3: Elastic layer
Claims
1. A siloxane composition comprising the following components (A) to (D): (A) an organopolysiloxane consisting of the following components (A-1) and (A-2): (A-1) Organopolysiloxane represented by the following average composition formula (1): 【Chemistry 1】 (In the average compositional formula (1), R 1 each independently represents an alkyl group having 1 to 10 carbon atoms; R 2 each independently represents an alkenyl group having 2 to 8 carbon atoms, and m is a number of 1,000 or more and 2,000 or less. (A-2) Organopolysiloxane represented by the following average composition formula (2): 【Chemistry 2】 (In average compositional formula (2), R 3 each independently represents an alkyl group having 1 to 10 carbon atoms; R 4 represents an alkenyl group having 2 to 8 carbon atoms for each repeating unit, о is a number of 10 or more and 45 or less, and n+о is a number of 300 or more and 500 or less.) (B) Specific surface area is 60 m 2 / g or more 100m 2 / g or less, (C) Specific surface area is 12 m 2 / g or more 30m 2 / g or less, (D) Organohydrogenpolysiloxane represented by the following average composition formula (3): 【Chemistry 3】 (In average compositional formula (3), R 5 each independently represents an alkyl group having 1 to 10 carbon atoms, p is a number of 3 or more and 20 or less, and q is a number of 4 or more and 20 or less. The ratio of the component (A-2) in the component (A) is 0.1% by mass or more and 5.0% by mass or less, a ratio (C2 / C1) of the content C2 of the second carbon black to the content C1 of the first carbon black is 2.0 or more and 25.0 or less; a total amount of the first carbon black and the second carbon black relative to the siloxane composition is 10% by mass or more and 30% by mass or less.
2. The second carbon black has a specific surface area of 20 m 2 / g or more 30m 2 2. The siloxane composition of claim 1, wherein the molecular weight of the siloxane composition is 1 / g or less.
3. 3. The siloxane composition according to claim 1, wherein in the average composition formula (2), o is a number of 15 or more and 25 or less.
4. The siloxane composition according to any one of claims 1 to 3, wherein the C2 / C1 is 5.0 or more and 10.0 or less.
5. 5. The siloxane composition according to claim 1, wherein the total amount of the first carbon black and the second carbon black relative to the siloxane composition is 10% by mass or more and 20% by mass or less.
6. 6. The siloxane composition according to claim 1, wherein the content of the second carbon black relative to the siloxane composition is 11% by mass or more and 15% by mass or less.
7. In the average composition formula (1), R 1 The siloxane composition according to any one of claims 1 to 6, wherein is a methyl group.
8. 8. An electrophotographic member having a substrate and an elastic layer on the substrate, the elastic layer being a cured product of the siloxane composition according to claim 1.
9. A method for producing an electrophotographic member having a substrate and an elastic layer on the substrate, the method comprising the step of curing a layer of the siloxane composition according to any one of claims 1 to 7 to form the elastic layer.
10. 9. A process cartridge comprising the electrophotographic member according to claim 8, said process cartridge being detachably mountable to a main body of an electrophotographic image forming apparatus.
11. 9. An electrophotographic image forming apparatus comprising: an image carrier for carrying an electrostatic latent image; a charging device for primarily charging the image carrier; an exposure device for forming an electrostatic latent image on the primarily charged image carrier; a developing device for developing the electrostatic latent image with toner to form a toner image; and a transfer device for transferring the toner image to a transfer material, wherein the developing device has the electrophotographic member according to claim 8.
Citation Information
Patent Citations
Intermediate transfer members
CN110249269A
fuser roller
DE3525545A1
Fixing roll
JP1986027574A
Compression-resistant silicone rubber composition
JP1992139258A
Electrically conductive roll
JP2001056018A
